2020
DOI: 10.7717/peerj.9801
|View full text |Cite
|
Sign up to set email alerts
|

Association of impaired fasting glucose and Type 2 Diabetes Mellitus with brain volume changes in Alzheimer’s Disease patients analyzed by MRI: a retrospective study

Abstract: Objectives Alzheimer’s disease (AD), impaired fasting glucose (IFG), and Type 2 diabetes mellitus (T2DM) were reported associated with smaller brain volumes. Nevertheless, the association of hyperglycemia with brain volume changes in AD patients remains unclear. To investigate this issue, structural magnetic resonance imaging was used to compare brain volumes among AD patients with different fasting glucose levels. Methods Eighty-five AD pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
1
2
0
1
Order By: Relevance
“…Similar to our research design, in structural MRI studies comparing AD patients with and without T2DM, it was reported that patients with AD and DM had significantly higher cortical atrophy caused by nonvascular mechanisms (Biessels et al, 2006) and significantly reduced pons volume (Wang et al, 2020). This research identified a significant impairment of the left SLF in AD patients with T2DM with DTI.…”
Section: Discussionsupporting
confidence: 84%
“…Similar to our research design, in structural MRI studies comparing AD patients with and without T2DM, it was reported that patients with AD and DM had significantly higher cortical atrophy caused by nonvascular mechanisms (Biessels et al, 2006) and significantly reduced pons volume (Wang et al, 2020). This research identified a significant impairment of the left SLF in AD patients with T2DM with DTI.…”
Section: Discussionsupporting
confidence: 84%
“…Different from other research software, AccuBrain ® is a fully automatic cloud-based computational tool, with no need for parameter settings during use ( Abrigo et al, 2019 ). More technical characteristics and their comparison with other automatic brain image segmentation methods were described in detail in previous work ( Gao et al, 2020 ; Wang et al, 2020 ). This tool has been validated to be more accurate, objective, and easier to implement and has been widely used in various neurological and mental diseases ( Wang et al, 2019 ; Zhao et al, 2019 ; Dou et al, 2020 ; Mai et al, 2021 ; Yu et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Accu-Brain® performs brain structure segmentation based on a multi-atlas image registration scheme. The accuracy of hippocampus segmentation of AccuBrain® was validated using data from the ADNI database [36], and more technical description of AccuBrain® and its comparison with other automatic brain image segmentation schemes were described in our previous work [37][38][39]. Since the main objective of this study is to identify FTD from NC and AD, we focus on the brain regions known to be associated with cognition and behavior, including the brain parenchyma, typical subcortical structures (bilateral hippocampus, amygdala and caudate, etc.…”
Section: Fig 1 Subject Screening From the Nacc Databasementioning
confidence: 99%